2017
DOI: 10.1186/s40560-017-0257-5
|View full text |Cite
|
Sign up to set email alerts
|

Lithium: one drug, five complications

Abstract: BackgroundLithium poisoning could trigger multiple complications. We report the case of a lithium poisoning with five complications that are described for the first time together.Case reportA 60-year-old woman was admitted in our intensive care unit for altered consciousness. Severe lithium intoxication was diagnosed (lithium plasmatic level 8.21 mmol/l) associated with acute oliguric kidney failure. Continuous renal replacement therapy was started immediately. Orotracheal intubation was quickly required becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…Lithium amount in dialysates correspond to 90% of total lithium excreted during CCVHF session while urine excretion account only for 10% during the same period. Our results proved the great efficacy of CCVDF and confirmed that the best method to treat severe lithium acute poisoning without plasma rebounds (5,12,13).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Lithium amount in dialysates correspond to 90% of total lithium excreted during CCVHF session while urine excretion account only for 10% during the same period. Our results proved the great efficacy of CCVDF and confirmed that the best method to treat severe lithium acute poisoning without plasma rebounds (5,12,13).…”
Section: Discussionsupporting
confidence: 76%
“…In return for its wide therapeutic use, lithium is still at the origin of numerous poisonings, mainly in a context of chronic drug accumulation, but self-administration of toxic doses may account for 20-27% of the hospitalized poisoning (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Intensive care unit admission with intubation may also be required during times that clinically suggest an impending central nervous system failure such as impaired consciousness, seizures and coma. 14…”
Section: Discussionmentioning
confidence: 99%
“…Konfusion, epileptische Anfälle) unterschieden [4]. Das klinische Bild einer Intoxikation kann zudem von internistischen und kardiologischen/ nephrologischen Symptomen überlagert werden [4][5][6][7].…”
Section: Diskussionunclassified